Phytolith evidence of historical rice cultivation at Wormsloe Historic Site, Georgia, USA. (August 2017) - Pasqua, Alessandro; da Costa, Liovando Marciano; Garrison, Ervan
Abstract: Despite much of the environmental history of Wormsloe Historic Site, Georgia, having been previously documented and described, the aspect related to whether rice cultivation was ever performed on-site still has not been entirely defined. The main goal of this study is the archaeobotanical investigation of soil samples collected from a salt marsh at Wormsloe where rice cultivation is suggested to provide a more definitive answer to this aspect. The study employs phytolith analysis to reveal evidence of past agricultural practices on-site related to rice cultivation. The results reveal the presence of phytoliths belonging to the rice genus, with some indicating a domesticated nature. Cultivation was likely done for subsistence purposes by the African American community living on the property. Preliminary radionuclide analysis suggests the soil samples may be older than 100 years. For the first time in Wormsloe's history, concrete evidence suggesting that rice was indeed cultivated on-site has been obtained, while also casting some light on local African American agricultural practices. The results of this study fill a gap in Wormsloe's environmental history, and increase Wormsloe's cultural, historical, and archaeological significance both at the regional and the national level. Ultimately, this study provides a reliable method to further investigate historical rice cultivation in other areas within the Wormsloe Site as well as along the southeastern United States. Highlights: Phytolith analysis suggests historical rice cultivation was performed on-site Rice cultivation at Wormsloe was performed for subsistence purposes by the African American population living on-site Preliminary radionuclide analysis suggests cultivation occurred around the turn of the 20 th century The results help fill a gap in Wormsloe's environmental history records The study increases Wormsloe's cultural, historical, and archaeological significance Further research on the property is needed to fully assess the significance of historical rice cultivation at Wormsloe